2021
DOI: 10.3390/polym13193282
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential Plasticizing Effect of Di-Carboxylic Acids for the Manufacturing of Solid Oral Forms with Copovidone and Ibuprofen by Selective Laser Sintering

Abstract: In selective laser sintering (SLS), the heating temperature is a critical parameter for printability but can also be deleterious for the stability of active ingredients. This work aims to explore the plasticizing effect of di-carboxylic acids on reducing the optimal heating temperature (OHT) of polymer powder during SLS. First, mixtures of copovidone and di-carboxylic acids (succinic, fumaric, maleic, malic and tartaric acids) as well as formulations with two forms of ibuprofen (acid and sodium salt) were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This allows predetermined and controlled release of drugs from sintered tablets. 36 Drug Content. The average drug content of DC and SLSmediated sintered tablets was found to be 90.06 ± 5.69 and 94.29 ± 6.29%, respectively.…”
Section: Methods Direct Compression (Dc)mentioning
confidence: 99%
“…This allows predetermined and controlled release of drugs from sintered tablets. 36 Drug Content. The average drug content of DC and SLSmediated sintered tablets was found to be 90.06 ± 5.69 and 94.29 ± 6.29%, respectively.…”
Section: Methods Direct Compression (Dc)mentioning
confidence: 99%
“…Interestingly, previous studies have also shown that drug release from SLS 3D printed drug products can be controlled by varying the drug load ( Fina et al, 2017 ), excipient type and load ( Allahham et al, 2020 ; Gueche et al, 2021a ), printlet geometry ( Fina et al, 2018a ) and laser scanning speed of the process ( Barakh Ali et al, 2019 ; Fina et al, 2018b ; Gueche et al, 2021b ; Khuroo et al, 2022 ). Fina.…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser sintering (SLS), one of the popular processes for manufacturing polymer materials in additive manufacturing technology, has continued to receive wide attention from the community in recent years [1,2]. In the polymer additive manufacturing process, polymer/fiber composite powder materials have attracted a lot of interest from scholars because fibers can significantly enhance the mechanical properties of the matrix material [3,4].…”
Section: Introductionmentioning
confidence: 99%